Usage of ABC Costing in Production Company - Karolina RYBICKA (Communications of International Proceedings, 2021)
In the conditions of the continuous-changing surrounding and continuous-increasing competition, the importance of cost accounting in a modern enterprise is systematically growing. Companies operate in increasingly difficult external conditions (progressing globalization of sales markets, shortening the life cycle of products, rapid development of information technology and technical progress), therefore they should be managed in the most effective way. Managers must give more and more attention to the optimization of costs related to their activity. Cost accounting must in the contemporary circumstances provide decision makers with complete and reliable cost data and allow control them at all management levels. The concept of cost calculation of manufactured goods was introduced and moved on to the costing considerations under the activity-based costing concept. The aim of the paper is to present – based on literature studies – definitions and issues connected with cost calculation There are used in the work following research methods: literature research as well as case study in production company of automotive industry.
Keywords: cost calculation; traditional costing; ABC costing